Dietary ketone ester attenuates the accretion of adiposity and liver steatosis in mice fed a high-fat, high-sugar diet - Rushing, Kelsey A.; Bolyard, Mickey L.; Kelty, Taylor; Wieschhaus, Nicole; Pavela, Gregory; Rector, R. Scott; Plaisance, Eric P. (Frontiers in Physiology, 2023)
Objective: The ketone diester, R,S-1,3-butanediol diacetoacetate (BD-AcAc2), attenuates the accretion of adiposity and reduces hepatic steatosis in high-fat diet-induced obese mice when carbohydrate energy is removed from the diet to accommodate energy from the ester. Reducing carbohydrate energy is a potential confounder due to the well-known effects of carbohydrate restriction on components of energy balance and metabolism. Therefore, the current investigation was designed to determine whether the addition of BD-AcAc2 to a high-fat, high-sugar diet (with no reduction in carbohydrate energy) would attenuate the accretion of adiposity and markers of hepatic steatosis and inflammation. Methods: Sixteen 11-week-old male C57BL/6J mice were randomized to one of two groups for 9 weeks (n = 8 per group): 1) Control (CON, HFHS diet) or 2) Ketone ester (KE, HFHS diet + BD-AcAc2, 25% by kcals). Results: Body weight increased by 56% in CON (27.8 ± 2.5 to 43.4 ± 3.7 g, p < 0.001) and by 13% in KE (28.0 ± 0.8 to 31.7 ± 3.1 g, p = 0.001). Nonalcoholic fatty liver disease activity scores (NAS) for hepatic steatosis, inflammation, and ballooning were lower in the KE group compared to CON (p < 0.001 for all). Markers of hepatic inflammation [Tnfα (p = 0.036); Mcp1 (p < 0.001)], macrophage content [(Cd68 (p = 0.012)], and collagen deposition and hepatic stellate cell activation [(αSma (p = 0.004); Col1A1 (p < 0.001)] were significantly lower in the KE group compared to CON. Conclusions: These findings extend those of our previous work and show that BD-AcAc2 attenuates the accretion of adiposity and reduces markers of liver steatosis, inflammation, ballooning, and fibrosis in lean mice placed on a HFHS diet where carbohydrate energy was not removed to accommodate energy from addition of the diester.